Pendampingan Kedisiplinan Santri Ma’hadusshibyan Melalui Sholat Dhuha Berjamaah - Ahmad Farid Muzammil; Faiz Amiruddin (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2021)
The purpose of this study is to describe 1) Implementation of Dhuha Prayer in Ma'hadusshibyan boarding school, 2) The Impact of Dhuha Jamaahmah Prayer Implementation on Improving Santri discipline in Ma'hadusshibyan boarding school. This type of research uses a qualitative approach with descriptive properties. While the data collection technique is done through observation, interview, and documentation. The results of the study showed that the Implementation of Dhuha Prayer in Ma'hadusshibyan boarding school was with the implementation of dhuha prayer carried out from 06.50 to 07.30, the habituation of congregational dhuha prayer was carried out with a spirited attitude by the santri, congregational dhuha prayer was done with an attitude of togetherness, and this congregational dhuha prayer was done through example (giving examples or good attitudes from teachers). While the impact of the implementation of Dhuha Prayer congregation to increase santri discipline in ma'hadusshibyan boarding school is as follows: Through the habituation of dhuha prayer can increase the attitude of discipline santri, through the habituation of dhuha prayer can increase religious attitude santri, Through the habituation of dhuha prayer can increase the attitude of responsibility on santri, and through the habituation of dhuha prayer can increase independent attitude.